An RF energy harvester - Wang, Chao (2017)
In recent years, use of wireless devices is growing in many applications like mobile phones and sensor networks. For those sensor networks, they are used in various scenarios such as intelligent monitoring systems for office, medical, or military applications. Currently, most of sensors are powered by batteries. But, as what we know, batteries still have a limited lifetime and their replacement is often complicated. This explains the necessity to find alternative ways to power these objects and harvesting energy from the ambient environment is a promising method. The harvesting equipment is aimed to supply power to low power devices especially for those installed in difficult access environment or places. This project aimed to design a 2.4GHz RF Energy Harvester, and finally the maximum RF-to-DC conversion efficiency of this prototype was measured at 6.0%, which the input power level was 15dBm. It produced a DC output voltage of 0.25V and 0.3uJ energy stored in the storage capacitor at an input power of 20dBm.